The influence of dementia on falls, gait and rehabilitation - Booth, Victoria (2017)
Background Cognitive impairment is a risk factor for falls in older adults. There is some evidence that the ability to dual-task contributes to maintaining postural stability and that cognitive impairment may impair this ability, thereby increasing falls risk. This research aims to explore physical risk factors associated with cognitive impairment and falls in older adults with mild dementia. Potential interventions for these participants will be searched for, described and theoretically modelled to develop an intervention programme to reduce their falls risk.